Heidegger and the notion of prescience (Vorwissenschaft) as existential propaedeutic. (Part 2: The extante of the death) - Ordóñez–García, José; Rüdinger, Kurt (Estudios de Filosofía, 2015)
Introduction. The following work is a continuation of an earlier one, ''Heidegger and the notion of prescience (Vorwissenschaft) as existential propaedeutic. (Part 1: The affection of the time)'' 2. Therefore, the reference source is also Heidegger conference Der Begriff der Zeit. But in this article we address the consequences of the binomial hermeneutical time / death without leaving the distinctive area of ''prescience''. Thus, further develop the implications of a knowledge that can not claim go beyond finitude. Methodology. We have developed this work by analyzing genealogical hermeneutic character based on the deployment of beingness. Results and conclusions. The existing lives the present installed in the presence of death, determining the here and now in the mode of a ''not yet'', which was established as the true being of time.